Menyemai Asa di Pegunungan Meratus: Peningkatan Kapasitas Masyarakat dalam Pengelolaan Kopi di Desa Batu Perahu Kabupaten Hulu Sungai Tengah - Nabawi, Ahmad; Hamid, Ismar; Sari, Dini Puspita; Syahputri, Arya Vernanda; Salsabila, Putri; Dani, Muhammad Anwaruddin; Febrianty, Nur'Aulia; Bahjah, Noor; Roji, Fkah; Irfan, Muhammad; Hairida, Gusti (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Coffee is one of the commodities in Batu Perahu Village, Batang Alai Timur District, Hulu Sungai Tengah Regency, which is located on the slopes of the Meratus Mountains. One of the reasons for the low economic growth in society is that the potential of coffee has not been maximized. Therefore, the service team implemented the program "Encouraging a Strategic Coffee Plantation Product Management Model in Batu Perahu Village". This program includes enabling, empowering and protecting which are then described in several activities, namely; 1) Coffee harvesting training; 2) Post-harvest coffee management training; 3) Procurement of post-harvest coffee management tools 4) Formation of farmer groups; 5) Branding Batu Perahu coffee; and 6) Building a marketing network for Batu Perahu coffee. Implementation of the program uses the live-in method in the village for 56 days, which runs from 18 July 2024 to 12 September 2024. The results achieved from this service program are increasing community capacity in harvesting coffee and managing post-harvest coffee which is supported by a pulper machine to support farmers coffee. As well as the formation of a coffee farmer group in Batu Perahu Village. In fact, Batu Perahu coffee already has branding with the name "Kopi Meratus" and also has a clear coffee marketing network. Through this program, the service team believes that the community's economy will improve in a sustainable manner, which has implications for the realization of coffee as a superior commodity and attraction of Batu Perahu Village.